REAKTUALISASI NILAI ISLAM DALAM BUDAYA MINANGKABAU MELALUI KEBIJAKAN DESENTRALISASI - Rahmat, Aulia (El-HARAKAH (TERAKREDITASI), 2011)
The decentralization have been represent the form of law development in pasca-reform 1998 era. Stipulate of regulation in Solok Sub-Province represents responsibility to this policy. Through this institution, the Minangkabauâs elite figure shown the integration of Islamic value with Minangkabauâs culture to maintain its individuality in modern era.Keyword : Desentralisasi, Islam dan Budaya Minangkabau.